Representasi Digital dan Akses Pengetahuan: Pengalaman Pengguna Tentang Sistem Informasi dalam Layanan Sosial - Anggraeni, Sherly Rosa (Jurnal Ilmiah Widya Sosiopolitika, 2025)
The high poverty rate in East Java illustrates not only economic inequality but also challenges in accessing inclusive and transparent social services. This study aims to examine how digital social service information systems represent knowledge and enable access from the perspective of everyday users. Using a qualitative exploratory case study approach, the research involved 15 informants such as students, housewives, and general citizens from three regions in East Java: Surabaya, Malang, and Trenggalek. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed thematically based on user experience. The findings reveal four key factors influencing users’ interactions with the system: accessibility, clarity of information, system responsiveness, and perceived benefits. Despite the availability of platforms such as SIKS-NG and cekbansos.kemensos.go.id, users encountered barriers such as unclear terminology, technical delays, and limited digital literacy, especially among vulnerable groups. These barriers often undermined the systems’ potential to promote inclusive access to public knowledge. The study concludes that user satisfaction and perceived usefulness are strongly determined by system quality and clarity of content. Therefore, the success of digital transformation in social services depends on the extent to which such systems are user-centered, inclusive, and context-sensitive.